Essays on economics of education - Marchi, Natália Zanetti (2020)
This thesis consists of three essays on economics of education. In the first chapter we investigate the effects of a reading and writing program on literacy development in early childhood education. To this end, we conducted a randomized study, including 44 intervention schools and 44 control schools. The main results indicate that the children who participated in the program outperformed the control children, especially in the measures of reading a 'rhyme' and writing words. Analysis of heterogeneous effects suggest that the intensity of treatment and the infrastructure of schools may reinforce the effects on the development of writing skills. In the second chapter our goal is to understand the relationship between peer influence and socioemotional skills. Using a database with information on students’ friendship ties, we first consider a traditional peer effects estimation model to identify endogenous and contextual effects. The evidence suggests negative endogenous effects for all measures (cognitive and socioemotional) and the presence of contextual effects of the socioemotional measure Self-Management on Language score. In our second exercise, we analyzed which characteristics most influenced the networking formation process and observed that, among cognitive and socioemotional skills, only homophily in terms of socioemotional skills increases the probability of two students becoming friends. Our third exercise explores the possibility of heterogeneous effects, analysing the role of the student’s position within the social network in the intensity of the effects. The results indicate that the student’s centrality is an important predictor of his academic results, even when we consider the average centrality of his peers. In the third chapter we investigate whether the implementation of a full-time high school program can affect the structure of the students’ friendship network. Using data from public school students in the State of Sergipe (Brazil), we identified that the program places the treated students in a more central position. In addition, we investigate whether this variation in the networks structure could be a channel through which the program affects students’ academic scores. The results of the model indicate that the individuals’ connectivity measures positively influence their math test scores, which suggests that there may be a mediation effect of the program on these scores that should be considered when assessing the policy’s results.